Composite ceramic material, method for the production and use thereof

CN118754720BActive Publication Date: 2026-10-09BEIJING INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410766010.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-14
Publication Date
2026-10-09
Estimated Expiration
2044-06-14

AI Technical Summary

Technical Problem

但是,碳化钨与磷化镍无法形成稳定的化学键合,并且二者热膨胀系数相差较大,模压过程中高温使磷化镍镀层的内应力增大,从而使磷化镍镀层开裂脱落

Benefits of technology

[0022] This invention also provides the application of the composite ceramic material described in the above-described scheme or the composite ceramic material prepared by the above-described scheme in precision glass molding. This invention improves the interfacial bonding force between the nickel phosphide plating and tungsten carbide through a micro-textured surface and transition layer, effectively reduces the internal stress of the nickel phosphide plating, and improves the high-temperature resistance of the composite ceramic material, enabling it to be used in precision glass molding and expanding the application range of composite ceramic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118754720B_ABST
    Figure CN118754720B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of composite materials, and particularly relates to a composite ceramic material and a preparation method and application thereof. The present application can increase the nucleation density of a nickel phosphide plating layer, reduce the number of micropores in the interface, and form a close interface bonding by increasing the specific surface area of the material through micro-texturing, thereby promoting the physical combination between the plating layer and the substrate, and solving the problem of poor interface bonding force between the nickel phosphide plating layer and tungsten carbide. The present application can enhance the interface bonding force by adding a transition layer between the nickel phosphide plating layer and tungsten carbide, and chemical bonding can occur at the interface between the transition layer and the nickel phosphide plating layer and tungsten carbide, and the thermal expansion coefficient of the transition layer is between that of the nickel phosphide and tungsten carbide, which can reduce the internal stress of the nickel phosphide, improve the high-temperature resistance of the nickel phosphide plating layer, solve the problem of mismatching of the thermal expansion coefficient and the crystal lattice between the two, further improve the interface bonding force of the plating layer, and improve the high-temperature resistance and chemical stability of the nickel phosphide plating layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite material technology, specifically relating to a composite ceramic material, its preparation method, and its application. Background Technology

[0002] Precision glass molding, as a method for mass production of glass optical components, relies on the precision of the molds used to directly determine the morphological accuracy of the glass. These molds typically use low-hardness materials, such as tungsten carbide plated with nickel phosphide, which has a hardness of 500-600 HV and good machinability, making them potential mold materials for precision glass molding.

[0003] Guo Weijia and colleagues at Beijing Institute of Technology optimized the process of electroless nickel phosphide plating on tungsten carbide by pretreating the tungsten carbide substrate with atmospheric pressure plasma, reducing the number of steps in electroless nickel phosphide plating, shortening the processing time, and improving the quality of the nickel phosphide plating. However, tungsten carbide and nickel phosphide cannot form a stable chemical bond, and their coefficients of thermal expansion differ significantly. The high temperature during molding increases the internal stress of the nickel phosphide plating, leading to cracking and peeling of the plating.

[0004] Therefore, the interfacial bonding force of nickel phosphide coating on tungsten carbide is poor and cannot meet the requirements of precision glass molding. Summary of the Invention

[0005] The purpose of this invention is to provide a composite ceramic material, its preparation method, and its application. The composite ceramic material provided by this invention has good bonding between the nickel phosphide coating and the tungsten carbide, meeting the requirements of precision glass molding.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] The present invention provides a composite ceramic material comprising a first surface layer, a transition layer, and a second surface layer disposed sequentially; the first surface layer is a tungsten carbide layer; the transition layer is one or both of a TiN layer and a TiAlN layer; the second surface layer is a nickel phosphide plating layer; the surface of the first surface layer in contact with the transition layer is a microtextured surface; the surface of the transition layer in contact with the second surface layer is a microtextured surface.

[0008] Preferably, the thickness of the first surface layer is greater than 1 cm.

[0009] Preferably, the groove depth of the microtextured surface of the first surface layer is 5 to 30 micrometers, the spacing between adjacent grooves is 75 to 120 micrometers, and the ratio of the groove width to the spacing between adjacent grooves is 0.7 to 0.8:1.

[0010] Preferably, the microtextured surface of the first surface layer is a linear textured surface, a rectangular textured surface, a concentric circle textured surface, or a sinusoidal textured surface.

[0011] Preferably, the thickness ratio of the transition layer to the first surface layer is greater than 2 to 5:30.

[0012] Preferably, the thickness ratio of the second surface layer to the transition layer is 30-50:2-5.

[0013] The present invention also provides a method for preparing the composite ceramic material described above, comprising the following steps:

[0014] (1) Laser surface texturing of tungsten carbide to obtain tungsten carbide with microtextured surface;

[0015] (2) Physical vapor deposition is performed on the microtextured surface of the tungsten carbide containing the microtextured surface to obtain a transition layer on the microtextured surface of the tungsten carbide; the thickness of the transition layer is less than the trench depth of the microtexture.

[0016] (3) Nickel phosphide is plated on the surface of the transition layer to obtain a composite ceramic material.

[0017] Preferably, the laser surface texture device is a Leonis-1064-50 laser with a wavelength of 1064nm, a power of 50W, a pulse energy of 500μJ, a pulse width of 10ps, a scanning speed of 500mm / s, and a scanning number of 20 to 60 times.

[0018] Preferably, the nickel phosphide plating is performed by: activating the surface of the transition layer and then performing electroless plating; the activation is acidic activation; the reagent used for acidic activation is a 10% (v / v) hydrochloric acid aqueous solution; the acidic activation is performed under water bath conditions; the temperature of the acidic activation is 60°C, and the activation time is 5 min; the reagents used for electroless plating include nickel sulfate, sodium hypophosphite, lactic acid, propionic acid, and thiourea; the temperature of the electroless plating is 88°C, and the cleaning time is 2 h.

[0019] The present invention also provides the application of the composite ceramic material described in the above-described scheme or the composite ceramic material obtained by the preparation method described in the above-described scheme in precision glass molding.

[0020] This invention provides a composite ceramic material. By increasing the specific surface area of ​​the material through microtexture, this invention can improve the nucleation density of the nickel phosphide coating, reduce the number of micropores at the interface, thereby forming a tight interfacial bond and promoting physical bonding between the coating and the substrate. This solves the problem of poor interfacial bonding between the nickel phosphide coating and tungsten carbide. Furthermore, by adding a transition layer between the nickel phosphide coating and tungsten carbide, this invention allows for chemical bonding at the interface between the transition layer and the nickel phosphide coating and tungsten carbide, thus enhancing the interfacial bonding. The thermal expansion coefficient of the transition layer is between that of nickel phosphide and tungsten carbide, reducing the internal stress of nickel phosphide and improving the high-temperature resistance of the nickel phosphide coating. This solves the problem of thermal expansion coefficient and lattice mismatch between the two materials, further improving the interfacial bonding and enhancing the high-temperature resistance and chemical stability of the nickel phosphide coating.

[0021] This invention also provides a method for preparing the composite ceramic material described above. This invention establishes a microtextured surface on the tungsten carbide surface using a laser, and then deposits a TiN or TiAlN transition layer on the microtextured surface via physical vapor deposition. Ti and W elements, as well as Ti and Ni elements, can interpenetrate and form chemical bonds, improving the bonding force between them. Furthermore, the microtextured surface is sufficiently rough to mechanically lock with the transition layer and the nickel phosphide plating, further enhancing the interfacial bonding force between the plating layers.

[0022] This invention also provides the application of the composite ceramic material described in the above-described scheme or the composite ceramic material prepared by the above-described scheme in precision glass molding. This invention improves the interfacial bonding force between the nickel phosphide plating and tungsten carbide through a micro-textured surface and transition layer, effectively reduces the internal stress of the nickel phosphide plating, and improves the high-temperature resistance of the composite ceramic material, enabling it to be used in precision glass molding and expanding the application range of composite ceramic materials. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 A three-dimensional view of the composite ceramic material provided by the present invention (before polishing);

[0025] Figure 2 A front view of the composite ceramic material provided by the present invention (after polishing);

[0026] Figure 3 These are the bonding performance test results of the composite ceramic materials prepared in the control group of this invention;

[0027] Figure 4 The results of the bonding performance tests at room temperature for the composite ceramic materials prepared in Examples 8-12 of this invention are shown.

[0028] Reference numerals: 1 is the first surface layer, 2 is the microtextured surface, 3 is the transition layer, and 4 is the second surface layer. Detailed Implementation

[0029] The present invention provides a composite ceramic material comprising a first surface layer, a transition layer, and a second surface layer disposed sequentially; the first surface layer is a tungsten carbide layer; the transition layer is one or more of a TiN layer and a TiAlN layer; the second surface layer is a nickel phosphide plating layer; the surface of the first surface layer in contact with the transition layer is a microtextured surface; the surface of the transition layer in contact with the second surface layer is a microtextured surface.

[0030] The composite ceramic material provided by the present invention includes a first surface layer; the thickness of the first surface layer is greater than 1 cm, more preferably 1 to 3 cm.

[0031] In this invention, the groove depth of the microtextured surface of the first surface layer is preferably 5-30 micrometers, more preferably 10-25 micrometers, and even more preferably 15-20 micrometers. The spacing between adjacent grooves is preferably 75-120 micrometers, more preferably 80-100 micrometers. The ratio of the groove width to the spacing between adjacent grooves is preferably 0.7-0.8:1, more preferably 0.72-0.78:1, and even more preferably 0.74-0.76:1.

[0032] In this invention, the microtextured surface of the first surface layer is preferably a linear textured surface (LT), a rectangular textured surface (RT), a concentric circle textured surface (CT), or a sinusoidal textured surface (ST).

[0033] The composite ceramic material provided by the present invention includes a transition layer; the thickness ratio of the transition layer to the first surface layer is preferably greater than 2 to 5:30.

[0034] In this invention, the groove depth of the microtextured surface of the transition layer is preferably 5 to 15 micrometers, more preferably 15 micrometers, the width is preferably 60 to 80 micrometers, more preferably 60 micrometers, and the spacing is preferably 75 to 120 micrometers, more preferably 80 to 100 micrometers.

[0035] In this invention, the microtextured surface of the transition layer is preferably a linear textured surface, a rectangular textured surface, a concentric circle textured surface, or a sinusoidal textured surface.

[0036] In this invention, when the transition layer is a TiN layer and a TiAlN layer, the first surface layer and the transition layer are preferably arranged sequentially as a first surface layer, a TiN layer and a TiAlN layer, or a first surface layer, a TiAlN layer and a TiN layer.

[0037] The composite ceramic material provided by the present invention includes a second surface layer; the thickness ratio of the second surface layer to the transition layer is preferably 30-50:2-5, more preferably 35-45:3-5, and even more preferably 38-42:3-4.

[0038] Figure 1 This is a three-dimensional structural view of the composite ceramic material provided by the present invention. Figure 2 The composite ceramic material provided by this invention has an overall structure of nickel phosphide plating / microtextured surface / transition layer / microtextured surface / tungsten carbide. This invention improves the interfacial bonding force between nickel phosphide plating and tungsten carbide through the microtextured surface and transition layer.

[0039] The present invention also provides a method for preparing the composite ceramic material described above, comprising the following steps:

[0040] (1) Laser surface texturing of tungsten carbide to obtain tungsten carbide with microtextured surface;

[0041] (2) Physical vapor deposition is performed on the microtextured surface of the tungsten carbide containing the microtextured surface to obtain a transition layer on the microtextured surface of the tungsten carbide; the thickness of the transition layer is less than the trench depth of the microtexture.

[0042] (3) Nickel phosphide is plated on the surface of the transition layer to obtain a composite ceramic material.

[0043] This invention describes laser surface texturing of tungsten carbide to obtain tungsten carbide with a microtextured surface. In this invention, the laser surface texturing device is preferably a Leonis-1064-50 laser, with a wavelength preferably 1064 nm, a power preferably 50 W, a pulse energy preferably 500 μJ, a pulse width preferably 10 ps, ​​a scanning speed preferably 500 mm / s, and the number of scans preferably 20–60, more preferably 40.

[0044] After obtaining tungsten carbide with a microtextured surface, the present invention performs physical vapor deposition on the microtextured surface of the tungsten carbide to obtain a transition layer on the microtextured surface of the tungsten carbide. In the present invention, grinding and ion bombardment are preferably performed sequentially before physical vapor deposition; the ion bombardment is preferably argon ion bombardment.

[0045] In this invention, the temperature of the ion bombardment is preferably 300-400°C, more preferably 350°C, the bias voltage is preferably 800V, and the bombardment time is preferably 10min.

[0046] In this invention, when the transition layer is TiN, the preferred ion bombardment pressure is 5 × 10⁻⁶. -3 When the transition layer is TiAlN, the preferred ion bombardment pressure is 5 × 10⁻⁶. -4 torr.

[0047] In this invention, the physical vapor deposition is preferably arc ion plating; when the transition layer is TiN, the target material for arc ion plating is preferably Ti, the distance between the substrate and the target is preferably 150 mm, and the gas pressure is preferably 2 × 10⁻⁶. -2 The preferred bias voltage is 100V, and the preferred base pressure is 8×10. -6 The preferred deposition temperature is 400℃, the preferred deposition atmosphere is nitrogen, the preferred deposition time is 60 min, the preferred arc voltage is 19V, and the preferred arc current is 60A; the purity of the Ti is preferably greater than 99.99%, more preferably 99.999%.

[0048] In this invention, when the transition layer is TiAlN, the target material for the arc ion plating is preferably a TiAl alloy, the mass ratio of TiN to Al is preferably 1:1, the distance between the substrate and the target material is preferably 200 mm, and the gas pressure is preferably 8 × 10⁻⁶ mm. -3 The preferred bias voltage is 100V, and the preferred base pressure is 6×10. -6 The preferred deposition temperature is 380℃, the preferred deposition time is 90 min, the preferred arc voltage is 17V, and the preferred arc current is 60A.

[0049] After obtaining the tungsten carbide / microtexture / transition layer, the present invention deposits nickel phosphide on the surface of the transition layer to obtain a composite ceramic material. In the present invention, the nickel phosphide deposition method is preferably electroless plating.

[0050] In this invention, the nickel phosphide plating is preferably performed by activating the surface of the transition layer before electroless plating.

[0051] In this invention, the surface of the transition layer is preferably cleaned before activation (referred to as the first cleaning); the first cleaning preferably includes ultrasonic cleaning (referred to as the first ultrasonic cleaning), alkaline degreasing, and ultrasonic cleaning (referred to as the second ultrasonic cleaning).

[0052] In this invention, the first ultrasonic cleaning is preferably performed by sequentially cleaning with anhydrous ethanol and then with water; the water is preferably deionized water; the volume ratio of the anhydrous ethanol to the water is preferably 1:1; the temperature of the first ultrasonic cleaning is preferably 25°C, and the cleaning time is preferably 10 min.

[0053] In this invention, the reagents used for alkaline degreasing preferably include sodium hydroxide, sodium carbonate, trisodium phosphate, and water; the concentration of sodium hydroxide is preferably 7.5 g / L; the concentration of sodium carbonate is preferably 35 g / L; the concentration of trisodium phosphate is preferably 15 g / L; the alkaline degreasing is preferably carried out under water bath conditions; the temperature of the alkaline degreasing is preferably 60°C, and the cleaning time is preferably 5 min.

[0054] In this invention, the reagent used for the second ultrasonic cleaning is preferably anhydrous ethanol and then water, in sequence; the water is preferably deionized water; the volume ratio of anhydrous ethanol to water is preferably 1:1; the temperature of the second ultrasonic cleaning is preferably 60°C, and the cleaning time is preferably 10 min.

[0055] In this invention, the activation is preferably acidic activation; the reagent used for acidic activation is a 10% (v / v) hydrochloric acid aqueous solution; the acidic activation is carried out under water bath conditions; the temperature of the acidic activation is 60°C, and the activation time is 5 min.

[0056] In this invention, the activation process preferably includes a second cleaning; the second cleaning is preferably ultrasonic cleaning (denoted as the third ultrasonic cleaning); the third ultrasonic cleaning preferably includes cleaning with anhydrous ethanol and water in sequence; the water is preferably deionized water; the volume ratio of anhydrous ethanol to water is preferably 1:1; the temperature of the first ultrasonic cleaning is preferably 88°C, and the cleaning time is preferably 10 min.

[0057] In this invention, the reagents used for the electroless plating preferably include nickel sulfate, sodium hypophosphite, lactic acid, propionic acid, and thiourea; the concentration of nickel sulfate is preferably 30 g / L; the concentration of sodium hypophosphite is preferably 20 g / L; the concentration of lactic acid is preferably 25 g / L; the concentration of propionic acid is preferably 5 g / L; the concentration of thiourea is preferably 0.001 g / L; the electroless plating temperature is preferably 88°C, and the cleaning time is preferably 2 hours.

[0058] In this invention, the electroless plating process preferably includes a third cleaning step; the third cleaning step is preferably ultrasonic cleaning (referred to as the fourth ultrasonic cleaning); the fourth ultrasonic cleaning step is preferably cleaning with anhydrous ethanol and then with water in sequence; the water is preferably deionized water; the volume ratio of anhydrous ethanol to water is preferably 1:1; the temperature of the first ultrasonic cleaning step is preferably 60°C, and the cleaning time is preferably 1 min.

[0059] The present invention also provides the application of the composite ceramic material described in the above-described scheme or the composite ceramic material obtained by the preparation method described in the above-described scheme in precision glass molding.

[0060] This invention improves the interfacial bonding force between nickel phosphide plating and tungsten carbide through microtextured surfaces and transition layers, effectively reduces the internal stress of nickel phosphide plating, and enhances the high-temperature resistance of composite ceramic materials, enabling them to be used as molds for precision glass molding and expanding the application range of composite ceramic materials.

[0061] To further illustrate the present invention, the following detailed description of the invention's solutions, in conjunction with the accompanying drawings and embodiments, is provided, but should not be construed as limiting the scope of protection of the present invention.

[0062] Example 1

[0063] This embodiment prepares a composite ceramic material, which consists of, from bottom to top, a tungsten carbide layer with a microtextured upper surface, a transition layer with a microtextured upper surface, and a nickel phosphide plating layer; the transition layer is a TiN layer.

[0064] The thickness of the tungsten carbide layer on the microtextured surface is 1 cm, the groove depth of the microtextured surface is 15 μm, the width is 60 μm, the spacing is 75 μm, and the type is linear texture.

[0065] The thickness ratio of the transition layer to the tungsten carbide layer on the microtextured surface is 15:10000. The grooves on the microtextured surface have a depth of 15 micrometers, a width of 60 micrometers, a spacing of 75 micrometers, and are of the linear texture type.

[0066] The thickness ratio of the nickel phosphide plating layer to the transition layer is 50:5.

[0067] The preparation method of the composite ceramic material in this embodiment includes the following steps:

[0068] (1) Laser surface texturing is performed on tungsten carbide. The laser surface texturing equipment is a Leonis-1064-50 laser with a wavelength of 1064nm, a power of 50W, a pulse energy of 500μJ, a pulse width of 10ps, a scanning speed of 500mm / s, and 60 scans to obtain tungsten carbide with a microtextured surface.

[0069] (2) After polishing the microtextured surface of the tungsten carbide, argon ion bombardment is performed. The argon ion bombardment temperature is 350℃, the bias voltage is 800V, and the gas pressure is 5×10⁻⁶. -3 The bombardment time was 10 min, followed by arc ion plating. The target material for arc ion plating was 99.99% pure Ti, the distance between the substrate and the target was 150 mm, and the gas pressure was 2 × 10⁻⁶. -2 Torr, bias voltage 100V, base pressure 8×10 -6The deposition temperature was 400℃, the deposition time was 60 min, the arc voltage was 19V, and the arc current was 60A to obtain a tungsten carbide / microtexture / transition layer.

[0070] (3) The transition layer surface was subjected to the following steps in sequence: ultrasonic cleaning at 25°C (using anhydrous ethanol and deionized water for 10 min), alkaline degreasing in a 60°C water bath (reagents were sodium hydroxide, sodium carbonate, trisodium phosphate and water, with sodium hydroxide concentration of 7.5 g / L, sodium carbonate concentration of 35 g / L and trisodium phosphate concentration of 15 g / L) for 5 min, ultrasonic cleaning at 60°C (using anhydrous ethanol and deionized water for 10 min), and acid activation in a 60°C water bath (reagent was 10% salt by volume). The composite ceramic material was obtained by ultrasonic cleaning at 88℃ for 5 min with an acidic aqueous solution (with anhydrous ethanol and deionized water for 10 min), electroless plating at 88℃ (the plating solution consisted of nickel sulfate, sodium hypophosphite, lactic acid, propionic acid, and thiourea, with nickel sulfate concentration of 30 g / L, sodium hypophosphite concentration of 20 g / L, lactic acid concentration of 25 g / L, propionic acid concentration of 5 g / L, and thiourea concentration of 0.001 g / L) for 2 h, and ultrasonic cleaning at 60℃ (with anhydrous ethanol and deionized water for 1 min).

[0071] Example 2

[0072] This embodiment prepares a composite ceramic material, which consists of, from bottom to top, a tungsten carbide layer with a microtextured upper surface, a transition layer with a microtextured upper surface, and a nickel phosphide plating layer; the transition layer is a TiAlN layer;

[0073] The thickness of the tungsten carbide layer on the microtextured surface is 1 cm, the groove depth of the microtextured surface is 15 μm, the width is 60 μm, the spacing is 75 μm, and the type is sinusoidal texture.

[0074] The thickness ratio of the transition layer to the tungsten carbide layer on the microtextured surface is 15:10000. The groove depth of the microtextured surface is 15 micrometers, the width is 60 micrometers, the spacing is 75 micrometers, and the type is sinusoidal texture.

[0075] The thickness ratio of the nickel phosphide plating layer to the transition layer is 30:2.

[0076] The preparation method of the composite ceramic material in this embodiment includes the following steps:

[0077] (1) Laser surface texturing is performed on tungsten carbide. The laser surface texturing equipment is a Leonis-1064-50 laser with a wavelength of 1064nm, a power of 50W, a pulse energy of 500μJ, a pulse width of 10ps, a scanning speed of 500mm / s, and 20 scans to obtain tungsten carbide with a microtextured surface.

[0078] (2) After polishing the microtextured surface of the tungsten carbide, argon ion bombardment is performed. The argon ion bombardment temperature is 350℃, the bias voltage is 800V, and the gas pressure is 5×10⁻⁶. -4 The bombardment time was 10 minutes, followed by arc ion plating. The target material for arc ion plating was a TiAl alloy, the distance between the substrate and the target was 200 mm, and the gas pressure was 8 × 10⁻⁶. -3 Torr, bias voltage 100V, base pressure 6×10 -6 The deposition temperature was 380℃, the deposition time was 90 min, the arc voltage was 17V, and the arc current was 60A, resulting in a tungsten carbide / microtexture / transition layer.

[0079] (3) The transition layer surface was subjected to the following steps in sequence: ultrasonic cleaning at 25°C (using anhydrous ethanol and deionized water for 10 min), alkaline degreasing in a 60°C water bath (reagents were sodium hydroxide, sodium carbonate, trisodium phosphate and water, with sodium hydroxide concentration of 7.5 g / L, sodium carbonate concentration of 35 g / L and trisodium phosphate concentration of 15 g / L) for 5 min, ultrasonic cleaning at 60°C (using anhydrous ethanol and deionized water for 10 min), and acid activation in a 60°C water bath (reagent was 10% salt by volume). The composite ceramic material was obtained by ultrasonic cleaning at 88℃ for 5 min with an acidic aqueous solution (with anhydrous ethanol and deionized water for 10 min), electroless plating at 88℃ (the plating solution consisted of nickel sulfate, sodium hypophosphite, lactic acid, propionic acid, and thiourea, with nickel sulfate concentration of 30 g / L, sodium hypophosphite concentration of 20 g / L, lactic acid concentration of 25 g / L, propionic acid concentration of 5 g / L, and thiourea concentration of 0.001 g / L) for 2 h, and ultrasonic cleaning at 60℃ (with anhydrous ethanol and deionized water for 1 min).

[0080] Example 3

[0081] This embodiment prepares a composite ceramic material using the same preparation method as in Example 1. The difference is that the thickness of the tungsten carbide layer on the microtextured upper surface is 1 cm, the groove depth of the microtextured surface is 15 μm, the width is 60 μm, and the spacing is 75 μm; the groove depth of the microtextured surface of the transition layer is 15 μm, the width is 80 μm, and the spacing is 100 μm.

[0082] Example 4

[0083] This embodiment prepares a composite ceramic material using the same preparation method as in Example 1, except that the groove depth of the tungsten carbide layer on the microtextured upper surface is 5, 10, or 15 micrometers.

[0084] Example 5

[0085] This embodiment prepares a composite ceramic material. The preparation method is the same as that in Example 1. The difference is that the microtexture surface of the tungsten carbide layer with microtexture is rectangular with a spacing of 120 micrometers and a trench depth of 5, 10 or 15 micrometers.

[0086] Example 6

[0087] This embodiment prepares a composite ceramic material. The preparation method is the same as that in Embodiment 1. The difference is that the microtexture surface of the first surface layer is a concentric circle texture with a spacing of 80 micrometers and a groove depth of 5, 10 or 15 micrometers.

[0088] Example 7

[0089] This embodiment prepares a composite ceramic material. The preparation method is the same as that in Example 1. The difference is that the microtexture surface of the tungsten carbide layer with microtexture is sinusoidal texture and the groove depth is 5, 10 or 15 micrometers.

[0090] Example 8

[0091] This embodiment prepares a composite ceramic material using the same preparation method as in Example 1, except that the tungsten carbide layer does not have a microtextured surface. The resulting composite ceramic material is denoted as TN1.

[0092] Example 9

[0093] This embodiment prepares a composite ceramic material. The preparation method is the same as that in Example 1. The difference is that the type of the microtextured surface of the tungsten carbide layer with microtextured upper surface is sinusoidal texture. The resulting composite ceramic material is denoted as TN2.

[0094] Example 10

[0095] This embodiment prepares a composite ceramic material using the same preparation method as in Example 1. The difference is that the tungsten carbide layer has no microtextured surface, and the transition layer is a TiAlN layer. The resulting composite ceramic material is denoted as TA1.

[0096] Example 11

[0097] This embodiment prepares a composite ceramic material. The preparation method is the same as in Example 1, except that the microtexture surface of the tungsten carbide layer with microtexture is sinusoidal texture, the transition layer is a TiAlN layer, and the resulting composite ceramic material is denoted as TA2.

[0098] Example 12

[0099] This embodiment prepares a composite ceramic material using the same preparation method as in Example 1, except that there is no transition layer; the groove depth of the tungsten carbide layer on the microtextured upper surface is 15 micrometers, and the resulting composite ceramic material is designated as ST-D15.

[0100] Referring to Examples 1 and 4-7, composite ceramic materials without only the transition layer were prepared as a control group, and their bonding performance was tested. The results are as follows: Figure 3 As shown. According to Figure 3 It can be seen that the interfacial bonding force of the composite ceramic material in the control group reached 15.11 MPa.

[0101] The bonding performance of the composite ceramic materials prepared in Examples 8-12 was tested using a pull-out test conducted on a UTM2503 universal testing machine. The results are as follows: Figure 4 As shown in Table 1.

[0102] Table 1. Test results of the bonding performance of composite ceramic materials in Examples 8-12

[0103]

[0104]

[0105] Note: In the table, "√" indicates that the coating is intact and undamaged; "×" indicates that the coating is cracked and peeling off; "*" indicates that the coating is cracked but not peeling off.

[0106] according to Figure 4 As can be seen from Table 1, the interfacial bonding strength of the second surface layer of the composite ceramic material of the present invention reaches 32.45 MPa, and it can maintain its complete morphology at a high temperature of 450℃, which is superior to ST-D15 without a transition layer.

[0107] As can be seen from the above embodiments, the composite ceramic material provided by the present invention has good bonding force between the nickel phosphide coating and tungsten carbide, reduces the internal stress of the nickel phosphide coating, improves the high temperature resistance of the nickel phosphide coating, and meets the requirements of precision glass molding.

[0108] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A composite ceramic material, characterized in that, It includes a first surface layer, a transition layer, and a second surface layer arranged sequentially; The first surface layer is a tungsten carbide layer; The transition layer is a TiN layer; The second surface layer is a nickel phosphide plating layer; The surface in contact with the transition layer of the first surface layer is a microtextured surface, and the microtextured surface of the first surface layer is a sinusoidal textured surface; The surface of the transition layer that contacts the second surface layer is a microtextured surface, and the microtextured surface of the transition layer is a sinusoidal textured surface.

2. The composite ceramic material according to claim 1, characterized in that, The groove depth of the microtextured surface of the first layer is 5 to 30 micrometers, the spacing between adjacent grooves is 75 to 120 micrometers, and the ratio of the groove width to the spacing between adjacent grooves is 0.7 to 0.8:

1.

3. The composite ceramic material according to claim 1, characterized in that, The thickness ratio of the second surface layer to the transition layer is 30~50:2~5.

4. The method for preparing the composite ceramic material according to any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Laser surface texturing of tungsten carbide to obtain tungsten carbide with microtextured surface; (2) Physical vapor deposition is performed on the microtextured surface of the tungsten carbide containing the microtextured surface to obtain a transition layer on the microtextured surface of the tungsten carbide; the thickness of the transition layer is less than the trench depth of the microtexture. (3) Nickel phosphide is plated on the surface of the transition layer to obtain a composite ceramic material.

5. The preparation method according to claim 4, characterized in that, The laser surface textured surface device is a Leonis-1064-50 laser with a wavelength of 1064nm, a power of 50W, a pulse energy of 500μJ, a pulse width of 10ps, a scanning speed of 500mm / s, and a scanning frequency of 20~60 times.

6. The preparation method according to claim 4, characterized in that, The nickel phosphide plating process involves activating the surface of the transition layer before electroless plating. The activation is acid activation; The reagent used for acid activation is a 10% (v / v) hydrochloric acid aqueous solution; The acid activation is carried out under water bath conditions; The acid activation temperature is 60℃, and the activation time is 5 min; The reagents used in the electroless plating include nickel sulfate, sodium hypophosphite, lactic acid, propionic acid, and thiourea. The electroless plating temperature is 88℃, and the cleaning time is 2 hours.

7. The application of the composite ceramic material according to any one of claims 1 to 3 or the composite ceramic material obtained by the preparation method according to any one of claims 4 to 6 in precision glass molding.

Citation Information

Patent Citations

  • Chemical plating solution for Ni-P plated layer and controllable preparation method of micro-nano mold

    CN106381482A

  • Matrix with enhanced bonding strength of surface coating and preparation method of matrix

    CN107761072A